Anchoring group regulation in semiconductor/molecular complex hybrid photoelectrode for photoelectrochemical water splitting - Xiangyan Chen; Fujun Niu; Tongxiang Ma; Qingyu Li; Shaopeng Wang; Shaohua Shen (Smart Molecules)
Abstract Rational interface engineering via regulating the anchoring groups between molecular catalysts and light‐absorbing semiconductors is essential and emergent to stabilize the semiconductor/molecular complex interaction and facilitate the photocarriers transport, thus realizing highly active and stable photoelectrochemical (PEC) water splitting. In this mini review, following a showcasing of the fundamental details of hybrid PEC systems containing semiconductor photoelectrodes and molecular catalysts for water splitting, the state‐of‐the‐art progress of anchoring group regulation at semiconductor/molecular complex interface for efficient and stable PEC water splitting, as well as its effect on charge transfer kinetics, are comprehensively reviewed. Finally, potential research directions aimed at building high‐efficiency hybrid PEC water splitting systems are summarized.